PROBLEMS OF YOUTH EMPLOYMENT IN THE COUNTRIES OF THE EURASIAN ECONOMIC UNION - Alena A. Petrochenko (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 3, Èkonomika,Èkologiâ, 2018)
The labor market is one of the most important spheres of the economy, one of the indicators on the basis of which we can evaluate the national prosperity, stability, and the effectiveness of social and economic transformations. In its turn, employment of the population is a necessary condition for society development and is one of the key elements influencing the living standards, staff training, material support for unemployed people. The youth is the most vulnerable category in the labor market. The article examines the labor market of the youth of the Eurasian Economic Union (EAEU). The level of youth unemployment is analyzed, and it is revealed that its lowest level in the EAEU countries falls on Kazakhstan, and the highest – on Armenia. The main programs promoting young people in the labor market are studied. The special attention is paid to the analysis of problems of youth employment in the EAEU countries. It is revealed that the following problems exist in the EAEU countries: the increase in the share of youth in the NEET category, the non-availability of graduates of higher school, the disparity between the skills of graduates and labor market demands, the migration of young people, and the high level of youth unemployment in Armenia. Based on the results of the study, the author proposes the creation of the Youth Employment Center of the Unified Energy System of the EAEU, whose main goal will be to improve the efficiency of management in the matter of young citizens employment in the EAEU countries; granting internships to the skilled students, providing benefits to companies employing young professionals without work experience.